The Genetics of the Dog (2nd Edition) - Ostrander, Elaine A (CABI, 2014)
The second edition of The Genetics of the Dog has been prepared for publication 10 years after the original version. This relatively short period of time has heralded an extraordinary degree of progress in canine genetics, and has seen our community move from the early stages of map building to the completion of large linkage and genome-wide association studies. The latter have allowed us to identify genes for disease susceptibility, behavioural traits and morphological fea- tures. In the last 10 years, a reference sequence of the Boxer dog was produced and dozens of genomes of other breeds are currently being sequenced using state-of-the-art high-throughput approaches. This progress in both genetics and genomics has led to the implementation of pow- erful laboratory methods which, together with the further advancement of bioinformatics, has produced the plethora of data available to students of mammalian biology and comparative genet- ics. For millennia, dogs have served humans in numerous ways. Most recently, however, the dog has become the model system of choice for the study of many human genetic disorders. In this edition, we have made an attempt to take all of these new developments into consideration. In doing so, not surprisingly, the chapter topics and the authors have changed significantly; the majority of chapters have been written by different authors. We believe that the final output is an improved product, with clarity of structure and updated content.